In Vitro Studies on Alpha-amylase Inhibitory Activities of Zanthoxylum armatum of Mid-Western Regions of Nepal - Dahal, Deepak; Subedee, Anup; Khanal, Kalpana; Basnyat, Ram Chandra (Amrit Research Journal, 2021)
The alpha-amylase inhibitors are used as a drug to control hyperglycemia in type II diabetes mellitus. The plant extract is a natural source to minimize toxicity and other side effects. The alpha-amylase inhibition assay shows that the methanol extracts of fruits, seeds, leaves, and barks of Z. armatum exhibit 50% alpha-amylase inhibition activity at concentration 47.73 μg/mL, 50.25 μg/mL, 67.25 μg/mL, 152.6 μg/mL respectively, and hexane extracts of fruits, seeds, leaves and barks of Z. armatum exhibits 50% alpha-amylase inhibition activity at concentration 86.24 μg/mL, 84.02 μg/mL, 98.8 μg/mL, 138.81 μg/mL respectively, whereas the 50% alpha-amylase inhibition activity of Acarbose (standard) was found to be 33.66 μg/mL. Therefore, methanol and hexane extracts of fruits, seeds, and leaves show potential alpha-amylase inhibition activity and can be used as anti-diabetes.